Burundi : 2010 Article IV Consultation and Fourth Review Under the Three-Year Arrangement Under the Extended Credit Facility and Request for Modification of Performance Criteria; Staff Report; Staff Supplement; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for Burundi. (IMF Staff Country Reports; Country Report, 2010)
The global financial crisis has slowed the Burundian economy and a significant decline in inflation. Against the background of the East African Community (EAC) integration, the Article IV Consultation discussions focused on three fundamental themes. IMF staff and authorities agreed on the need to pursue appropriate growth-enhancing reforms. The authorities and staff agreed on the need to continue reforms of wages and employment to bring the wage bill down to sustainable levels. The fourth review was completed based on Burundi's performance and the strength of the program.